Mortality of Sepsis in Patients With Rheumatoid Arthritis: A Single-Center Retrospective Analysis and Comparison With a Control Group. (July 2021) - Krasselt, Marco; Baerwald, Christoph; Petros, Sirak; Seifert, Olga
Introduction/Background: Patients with rheumatoid arthritis (RA) have a high risk of infections that may require intensive care unit (ICU) admission in case of resulting sepsis. Data regarding the mortality of these patients are very limited. This study investigated clinical characteristics and outcomes of patients with RA admitted to the ICU for sepsis and compared the results to a control cohort without RA. Methods: All patients with RA as well as sex-, age-, and admission year-matched controls admitted to the ICU of a university hospital for sepsis between 2006 and 2019 were retrospectively analyzed. Mortality was calculated for both the groups, and multivariate logistic regression was used to determine independent risk factors for sepsis mortality. The positive predictive value of common ICU scores was also investigated. Results: The study included 49 patients with RA (mean age 67.2 ± 9.0 years, 63.3% females) and 51 matched controls (mean age 67.4 ± 9.5 years, 64.7% females). Among the patients with RA, 42.9% (n = 21) were treated with conventional synthetic (cs) disease-modifying antirheumatic drugs (DMARDs) and 30.6% (n = 15) received glucocorticoids only. Seven (14.3%) patients received biologic (b) DMARDs. The hospital mortality was higher among patients with RA (42.9% vs 15.7%, P = .0016). Rheumatoid arthritis was independently associated with mortality in multivariate logistic regression ( P = .001). In patients with RA, renal replacement therapy ( P = .024), renal failure ( P = .027), and diabetes mellitus ( P = .028) were independently associated with mortality. Acute Physiology and Chronic Health Evaluation II (APACHE II), Simplified Acute Physiology Score II (SAPS II), and Sequential Organ Failure Assessment (SOFA) scores were good predictors of sepsis mortality in patients with RA (APACHE II area under the curve [AUC]: 0.78, P = .001; SAPS II AUC: 0.78, P < .001; SOFA AUC 0.78, P < .001), but their predictive power was higher among controls. Conclusions: Hospital sepsis mortality was higher in patients with RA than in controls. Rheumatoid arthritis itself is independently associated with an increased sepsis mortality. Renal replacement therapy, renal failure, and diabetes were associated with an increased mortality. Common ICU scores were less well predictors of sepsis mortality in patients with RA compared to non-RA controls.